Tearable aerosol coating and preparation method thereof
Through an innovative combination of tearable aerosol coatings, the insufficient protection of mechanical sealants and the environmental problems of traditional coatings are solved, providing wear resistance and rust prevention, improving the protection of industrial components and equipment lifespan, and making it suitable for home appliances and industrial production.
Patent Information
- Application Number
- CN202510216437.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-10-28
AI Technical Summary
Existing mechanical sealing films are insufficient in their protective capabilities during transportation and transfer, which can easily lead to rust and discoloration of products. Furthermore, traditional coatings have environmental problems and insufficient wear resistance, failing to effectively protect industrial components and affecting equipment lifespan and production efficiency.
A peelable aerosol coating is used, which includes water-based peelable emulsion, wear-resistant glass fiber powder, solid graphite fiber lubricant and other components to form an environmentally friendly coating system. It has anti-rust, wear-resistant and peelable properties and is suitable for the protection of industrial parts.
It achieves environmentally friendly, wear-resistant, and peelable coating protection, extends equipment life, reduces cleaning costs, improves mechanical efficiency, and meets environmental regulations.
Abstract
Description
Technical Field
[0001] This invention relates to the field of aerosol and functional paint technology, and in particular to a tearable aerosol coating and its preparation method. Background Technology
[0002] Within the realm of home appliance and related industrial manufacturing, there is also a broad social division of labor in manufacturing, and corresponding components are gradually moving towards modular production and manufacturing models. This division of labor has given rise to frequent logistics demands between upstream and downstream sectors. For example, in the logistics process of home appliances and related industrial products, there are unique marking and protection requirements.
[0003] Home appliances and related industrial products have extremely stringent requirements for appearance integrity, striving for 100% perfection. This gives rise to a very high demand for appearance protection processes, especially for components such as electronic displays, precision electroplating, and colored plastics, which are more fragile than other industrial components and require more careful handling. In the context of industrial clusters and modularization, various components need to be transported and transferred safely and with good quality through logistics. In this process, adequate and effective protection is particularly crucial.
[0004] Currently, the main protective measure used during transportation and transfer is mechanical sealing. While mechanical sealing offers certain operational convenience, its limitations become apparent when dealing with uneven surfaces. Mechanical sealing often suffers from deficiencies in protection, waterproofing, and rust prevention. Due to its interfaces and spaces, water or moisture can easily become a cause of product malfunctions, leading to frequent rusting and other defects. In fact, existing products have serious functional defects, lacking effective corrosion and rust prevention properties. During the storage, transportation, and use of industrial equipment and components, they are highly susceptible to corrosion from oxygen, moisture, acids, and alkalis in the surrounding environment. Lacking necessary anti-corrosion and rust prevention mechanisms, they exhibit obvious signs of corrosion within a very short time. This lack of short-term corrosion protection directly causes a sharp decline in the appearance and performance of equipment and components, significantly shortening their service life. For example, some metal parts, if not properly protected, will begin to rust and discolor after only a few days of storage. This not only damages the product's appearance but also significantly reduces its mechanical properties, such as strength and hardness, thus negatively impacting the normal operation and efficiency of the entire equipment and increasing the company's maintenance costs and downtime risks.
[0005] Compared to mechanical sealing, protective coatings can address issues such as uneven adhesion, bubbling, and surface delamination. However, mechanical sealing has a limited function, cannot withstand wear during logistics, its thickness is difficult to control precisely, and multi-layer application is fraught with challenges. Existing products lack a matching solid lubricant, making rapid, complete peeling difficult. Furthermore, they lack abrasion resistance and have poor toughness, making them unable to withstand impact. In real-world industrial production and applications, equipment and components are frequently subjected to various frictions and collisions. Due to the lack of abrasion resistance, the coating is easily worn away when in contact with other objects, thus losing its protective function. Simultaneously, insufficient toughness means that even minor impacts or vibrations can cause cracking and peeling, making it unable to withstand greater impacts. For example, during the operation of machinery, internal components rub and collide with each other. If the coating cannot provide sufficient abrasion and impact protection, the surface of the components will be rapidly damaged, affecting the precision and reliability of the equipment, potentially leading to equipment failure, production interruptions, and significant economic losses for the company.
[0006] To address these issues, engineers proposed a coating-based process, leading to a demand for composite functional reflective marking coatings. CN202310275694.9, "Tearable Masking Film Coating and its Preparation Method, and Method for Preparing Coated Patterned Glass Using Tearable Masking Film Coating," while a promising method for protection and application, still has limitations in practical use. In the current field of industrial product protection and application, many challenges urgently need to be overcome. Firstly, most existing products generally use oil-based coating systems combined with non-environmentally friendly propellants. Oil-based coating systems contain large amounts of volatile organic compounds (VOCs), which volatilize into the air during use. Inhalation of these substances can damage the respiratory and nervous systems, causing symptoms such as coughing, dizziness, and fatigue. Long-term exposure may even increase the risk of cancer. Furthermore, non-environmentally friendly propellants, such as some chlorofluorocarbons (CFCs), once released into the atmosphere, can damage the ozone layer, exacerbate global warming, severely disrupt the balance of the entire ecological environment, affect the survival and reproduction of plants and animals, and lead to a reduction in biodiversity. This characteristic, which is unfriendly to both humans and the environment, poses a significant challenge to existing products in the face of increasingly stringent environmental protection requirements.
[0007] However, current methods still suffer from drawbacks such as relatively complex processes and difficulty in removal, thus failing to meet existing demands. Given that water-based coatings represent a major development trend, and can strengthen coatings by improving resistivity, flexibility, protective properties, impact resistance, and tearability, it is evident that developing a water-based, environmentally friendly aerosol coating product that offers a tough film, convenient application, easy removal, and includes a temporary special indicator is of paramount practicality and necessity. This will provide strong support for the protective needs of the home appliance and related industrial manufacturing sectors, driving innovation and progress in protective technology across the entire industry. Water-based, environmentally friendly aerosol coating products possess significant practicality and necessity. Summary of the Invention
[0008] The purpose of this invention is to provide a tearable aerosol coating and its preparation method, thereby solving the above-mentioned problems.
[0009] To achieve the above objectives, the present invention provides a tearable aerosol coating comprising the following raw materials by weight: 15-19 parts of water-based peelable emulsion PVA 6-9 parts 14-20 parts of wear-resistant glass fiber powder 3-6 parts of solid graphite fiber lubricant 3-7 parts of surface treatment agent 4-7 parts of water-based rust inhibitor 1-4 parts release agent Thickener 0.4–0.8 parts 6-10 parts ethanol 5-9 parts water F152a 18-25 copies.
[0010] Preferably, the water-based peelable emulsion is an aliphatic polyurethane, and is at least one of Guangdong Honeycomb Nanomaterials and Guangdong Dongdun New Materials SEAPUR 50K05.
[0011] Preferably, the PVA is a water-soluble fiber.
[0012] Preferably, the wear-resistant glass fiber powder includes glass fibers with a diameter of 10-20 μm and PVC nanofiber powder with a diameter of 1-100 nm, and the weight ratio of glass fibers to PVC nanofiber powder is (2-5):(1-3).
[0013] Preferably, the solid lubricant is composed of polytetrafluoroethylene, thermoplastic resin, molybdenum disulfide, graphite, and epoxy resin, and is at least one of Celanese 3300-2, Shanghai Weixin Trading NW-02, and Shanghai Dirun Chemical 50EP.
[0014] Preferably, the surface treatment agent is at least one of (N,N-dimethylaminopropyl)-aminopropylmethyldimethoxysilane and (N,N-dimethyl-3-aminopropyl)trimethoxysilane.
[0015] Preferably, the water-based rust inhibitor is at least one of water-based zinc powder and water-based aluminum powder.
[0016] Preferably, the release agent is at least one of polytetrafluoroethylene modified polyethylene wax micro powder, high-density polyethylene wax, and water-based polyethylene wax emulsion.
[0017] Preferably, the thickener is at least one of a nonionic polyurethane thickener or a hydroxyethyl cellulose-based thickener.
[0018] This invention also provides a method for preparing the above-mentioned peelable aerosol coating, comprising the following steps: according to the weight ratio, heat the wear-resistant glass fiber powder and solid graphite fiber lubricant at 55-70℃ for 1-2 hours to dehydrate and mix them evenly; add a surface treatment agent for surface modification; add PVA, water-based peelable emulsion, water-based rust inhibitor, release agent, thickener, ethanol, and water to disperse and mix evenly to obtain a coating base material; according to the weight ratio, dispense the coating base material into an aerosol can, seal it, and fill it with F152a to obtain the finished product.
[0019] Therefore, this invention constructs an innovative water-based coating system, combined with an environmentally friendly propellant, which is not only friendly to humans and the environment, but also exhibits significant advantages in multiple performance aspects. Specifically: (1) This coating system uses environmentally friendly raw materials and does not contain harmful solvents or volatile organic compounds (VOCs), ensuring safety during construction and use, and meeting the current strict environmental protection regulations.
[0020] (2) By introducing an advanced rust inhibitor system, this product can effectively resist oxidation and corrosion of metal surfaces and extend the service life of equipment. It is especially suitable for long-term protection in harsh environments such as outdoors.
[0021] (3) The addition of wear-resistant fiber powder and reinforcing fibers to the formula significantly improves the toughness, impact resistance and wear resistance of the coating film. This enables the coating to remain intact under high stress conditions and reduces damage caused by external forces.
[0022] (4) The unique combination of graphite fiber and water-based metal rust inhibitor imparts extremely low resistivity and excellent lubrication properties to the coating. This characteristic is particularly important for applications requiring good conductivity and helps reduce friction and improve mechanical efficiency.
[0023] (5) This coating system also has unique peelable properties, which can be quickly separated from the substrate under certain conditions, making it easy to maintain and update, simplifying the subsequent processing procedures and reducing cleaning costs.
[0024] The technical solution of the present invention will be further described in detail below through embodiments. Detailed Implementation
[0025] The technical solution of the present invention will be further described below through embodiments.
[0026] Unless otherwise defined, the technical or scientific terms used in this invention shall have the ordinary meaning as understood by one of ordinary skill in the art to which this invention pertains. Example 1
[0027] This embodiment provides a tearable aerosol coating, the preparation process of which includes the following steps: According to the weight ratio, 10 parts of China Jushi Group 560A, 4 parts of Formosa Plastics Industrial (Ningbo) Co., Ltd. PVC nanofiber powder No. S-65, 2 parts of Celanese 3300-2, 2 parts of Shanghai Weixin Trading NW-02, and 2 parts of Shanghai Dirun Chemical 50EP are heated to 70℃ for dehydration for 1 hour and mixed evenly. Then, 4 parts of (N,N-dimethylaminopropyl)-aminopropylmethyldimethoxysilane, 3 parts of (N,N-dimethyl-3-aminopropyl)trimethoxysilane, 6 parts of PVA, 10 parts of Guangdong Honeycomb Nanomaterials 177-F8107, 9 parts of Guangdong Dongdun New Materials SEAPUR 50K05, 2 parts of water-based zinc powder, 2 parts of water-based aluminum powder, 1 part of Nanjing Tianshi PEW0221, 1 part of German Keim-Additec E-842N, and BASF Joncryl-wax 35 are added. 1.4 parts of Zhongwan TF-1003COATEX, 0.2 parts of Gaotai VISCOATEX 46, 0.2 parts of Gaotai VISCOATEX 730, 10 parts of ethanol, and 5 parts of water were dispersed and mixed evenly to obtain the coating base. The coating base was then packaged into aerosol cans according to the weight ratio, sealed, and filled with 25 parts of F152a to obtain the finished product. Example 2
[0028] This embodiment provides a tearable aerosol coating, the preparation process of which includes the following steps: According to the weight ratio, 14 parts of China Jushi Group 560A, 6 parts of Formosa Plastics Industrial (Ningbo) Co., Ltd. PVC nanofiber powder No. S-65, 2 parts of Celanese 3300-2, 0.5 parts of Shanghai Weixin Trading NW-02, and 0.5 parts of Shanghai Dirun Chemical 50EP were heated to 55℃ for dehydration for 2 hours and mixed evenly. Then, 1 part of (N,N-dimethylaminopropyl)-aminopropylmethyldimethoxysilane, 2 parts of (N,N-dimethyl-3-aminopropyl)trimethoxysilane, 9 parts of PVA, 16 parts of Guangdong Honeycomb Nanomaterials 177-F8107, 2 parts of Guangdong Dongdun New Materials SEAPUR 50K05, 4 parts of water-based zinc powder, 3 parts of water-based aluminum powder, 1 part of Nanjing Tianshi PEW0221, 0.3 parts of German Keim-Additec E-842N, and BASF Joncryl-wax 35 were added. 0.2 parts of Zhongwan TF-1003COATEX, 0.3 parts of Gaotai VISCOATEX 46, 0.1 parts of Gaotai VISCOATEX 730, 6 parts of ethanol, and 9 parts of water were dispersed and mixed evenly to obtain the coating base. The coating base was then packaged into aerosol cans according to the weight ratio, sealed, and filled with 23 parts of F152a to obtain the finished product. Example 3
[0029] This embodiment provides a tearable aerosol coating, the preparation process of which includes the following steps: According to the weight ratio, 8.5 parts of China Jushi Group 560A, 8.5 parts of Formosa Plastics Industrial (Ningbo) Co., Ltd. PVC nanofiber powder No. S-65, and 6 parts of Celanese 3300-2 were heated to 65℃ for 1.5 hours to dehydrate and mix evenly. Then, 5 parts of (N,N-dimethylaminopropyl)-aminopropylmethyldimethoxysilane, 8 parts of PVA, 18 parts of Guangdong Honeycomb Nanomaterials 177-F8107, 7 parts of water-based zinc powder, 3.2 parts of German Keim-Additec E-842N, 0.8 parts of Gaotai VISCOATEX 46, 10 parts of ethanol, and 7 parts of water were dispersed and mixed evenly to obtain the coating base. The coating base was then packaged into aerosol cans according to the weight ratio, sealed, and filled with 18 parts of F152a to obtain the finished product.
[0030] Comparative Example 1 This comparative example is a commercially available aerosol coating with poor tearability. The main components are formulated by weight as follows: 30 parts alkyd resin, 40 parts mixed solvent of butanol and acetone, approximately 20 parts organic pigment, and 10 parts plasticizer and anti-aging agent.
[0031] Comparative Example 2 This comparative example is a commercially available non-tearable aerosol paint. The main components are formulated by weight as follows: 35 parts acrylic resin, 45 parts mixed solvent of xylene and ethyl acetate, 15 parts inorganic pigments such as titanium dioxide and carbon black, and 5 parts leveling agent and defoamer.
[0032] Performance testing The tearable aerosol coatings prepared in Examples 1 to 3 of this invention and the conventional commercially available products in Comparative Examples 1 and 2 were used as samples for performance testing. The above examples and a commercially available zinc-rich primer were made into plates according to the requirements of HG / T 3668-2009 "Zinc-Rich Primer". The test methods for each performance are as follows. 1. Test the film performance according to the requirements of BB / T 0047-2018 "Aerosol Paint"; 2. Tearability of the paint film: Turpentine solvent is applied to the surface of the tearable aerosol paint film. The solvent dissolves the resin, reducing its adhesion to the substrate. When peeled off, no adhesive residue or damage to the substrate surface is left. The peeled paint film should remain intact, without breaking or peeling off. 3. Surface drying time: Refer to the provisions of GB / T 1728-1979 "Determination of Drying Time of Paint Film and Putty Film"; 4. Adhesion: The adhesion shall be determined in accordance with the provisions of GB / T 1720-1979(89) "Determination of Adhesion of Paint Film"; 5. Salt spray resistance: The test shall be conducted in accordance with the provisions of GB / T 1771-2007 "Determination of resistance to neutral salt spray of paints and varnishes"; 6. Surface resistivity: Measured according to GB / T 16906-1997 "Method for Determination of Resistivity of Conductive Coatings for Petroleum Tanks"; The performance test results are shown in Table 1 below: Table 1 Performance test results of 5 samples project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Drying time (min) 7 7 8 15 20 Adhesion (Grade) 1 1 1 2 3 Storage stability The paint sprayed out with good atomization. The paint sprayed out with good atomization. The paint sprayed out with good atomization. Zinc powder settles and clumps. Zinc powder settles and clumps. Tearability Can be completely torn off Can be completely torn off Can be completely torn off Partial tearing Do not tear Salt spray resistance (h) 1300 (No bubbles, no rust, no peeling) 1400 (No bubbles, no rust, no peeling) 1200 (No bubbles, no rust, no peeling) 300 (No bubbles, no rust, no peeling) 600 (No bubbles, no rust, no peeling) Surface resistivity (Ω) <![CDATA[10 7 ]]> <![CDATA[10 7 ]]> <![CDATA[10 8 ]]> <![CDATA[10 9 ]]> <![CDATA[10 9 ]]> The test results above show that the tearable aerosol coating prepared by this invention has the advantages of convenient construction, good anti-settling properties of the liquid, good environmental performance, long storage stability, good tearability, low resistivity, and excellent rust prevention performance, and can be widely used in various scenarios.
[0033] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A tearable aerosol coating, characterized in that, Raw materials comprising the following weight components: 15-19 parts of water-based peelable emulsion PVA 6-9 parts 14-20 parts of wear-resistant glass fiber powder 3-6 parts of solid graphite fiber lubricant 3-7 parts of surface treatment agent 4-7 parts of water-based rust inhibitor 1-4 parts release agent Thickener 0.4–0.8 parts 6-10 parts ethanol 5-9 parts water F152a 18-25 copies.
2. The tearable aerosol coating according to claim 1, characterized in that, The water-based peelable emulsion is an aliphatic polyurethane.
3. The tearable aerosol coating according to claim 1, characterized in that, The PVA is a water-soluble fiber.
4. The tearable aerosol coating according to claim 1, characterized in that, The wear-resistant glass fiber powder includes glass fibers with a diameter of 10-20μm and PVC nanofiber powder with a diameter of 1-100nm, and the weight ratio of glass fibers to PVC nanofiber powder is (2-5):(1-3).
5. The tearable aerosol coating according to claim 1, characterized in that, The solid lubricant is composed of polytetrafluoroethylene, thermoplastic resin, molybdenum disulfide, graphite, and epoxy resin.
6. The tearable aerosol coating according to claim 1, characterized in that, The surface treatment agent is at least one of (N,N-dimethylaminopropyl)-aminopropylmethyldimethoxysilane and (N,N-dimethyl-3-aminopropyl)trimethoxysilane.
7. The tearable aerosol coating according to claim 1, characterized in that, The water-based rust inhibitor is at least one of water-based zinc powder and water-based aluminum powder.
8. The tearable aerosol coating according to claim 1, characterized in that, The release agent is at least one of polytetrafluoroethylene modified polyethylene wax micro powder, high-density polyethylene wax, and water-based polyethylene wax emulsion.
9. The tearable aerosol coating according to claim 1, characterized in that, The thickener is at least one of a nonionic polyurethane thickener or a hydroxyethyl cellulose-based thickener.
10. A method for preparing a tearable aerosol coating as described in any one of claims 1-9, characterized in that, The process includes the following steps: according to the weight ratio, heat the wear-resistant glass fiber powder and solid graphite fiber lubricant at 55-70℃ for 1-2 hours to dehydrate and mix them evenly; add a surface treatment agent for surface modification; add PVA, water-based peelable emulsion, water-based rust inhibitor, release agent, thickener, ethanol, and water and mix them evenly to obtain a coating base; according to the weight ratio, dispense the coating base into an aerosol can, seal it, and fill it with F152a to obtain the finished product.
Citation Information
Patent Citations
Tearable masking film coating and preparation method thereof, and method for preparing coated patterned glass by using tearable masking film coating
CN116285542A